Mild regiospecific alcoholysis and aminolysis of epoxides catalyzed by zirconium(IV) oxynitrate - Shinde, Sandip S.; Said, Madhukar S.; Surwase, Trupti B.; Kumar, Pradeep (Tetrahedron Letters, 2015)
A regiospecific method for the ring-opening reaction of epoxides by the primary, secondary, tertiary alcohols, and aryl, aliphatic amines has been developed using non-toxic metal nitrate salt as a catalyst. The best results were obtained using zirconium(IV) oxynitrate among the various screened metal nitrate salts. The reported protocol works efficiently for styrene epoxide and aliphatic as well. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Alcoholysis; Aminolysis; Epoxide; Lewis acid; Zirconia